Alterations of Hematologic and Hematopoietic Parameters in Mice Exposed to Pulsed Electromagnetic Field - Kangchu Li; Zenghui Teng; Zhaohui Liu; Yuxing Zhang; Kaiping Long; Qimei Liao; Ansheng Ni; Guirong Ding; Shirong Ma (Journal of Immunology Research, 2019)
Effects of pulsed electromagnetic field (PEMF) on hematology and hematopoiesis might vary with different PEMF parameters. The purpose of this study was to evaluate the possible effects of PEMF exposure at different pulses on hematologic and hematopoietic parameters in mice. Groups of male BALB/c mice were whole body exposed or were sham exposed (control) to PEMF at 100, 1000, and 10000 pulses. After PEMF exposure, blood samples and bone marrow cells of mice were collected for hematologic examinations, bone marrow nucleated cell counting, colony-forming units of granulocyte-macrophage (CFU-GM) colony assay, and serum granulocyte-macrophage colony-stimulating factor (GM-CSF) assay. Compared with the control group, white blood cells (WBC) and lymphocytes (LYM) in the 100 and 1000 pulses exposed groups were significantly increased but not changed in the 10000 pulses exposed group. Red blood cells (RBC), hemoglobin (HGB), and platelets (PLT) were not changed in all exposed groups. There was no significant difference in mouse bone marrow nucleated cell number between the control group and each exposed group 7 days after PEMF exposure. The CFU-GM clone number of bone marrow cells and serum GM-CSF level were significantly increased in the 100 and 1000 pulses exposed group but not changed in the 10000 pulses exposed group. Our results indicated that the PEMF exposure at fewer pulses may induce statistically significant alterations in some hematologic and hematopoietic parameters of mice but no changes can be found in the more pulses PEMF-exposed groups.